Inconsistencies in International Product Strategies and Performance of High-Tech Firms. Issue 3 (September 2014) - Li, Lee; Qian, Gongming; Qian, Zhengming
This article explores two unresolved issues in the international business literature. First, it is not clear why high-tech firms should standardize their product strategies across countries. Second, the rationale for high-tech firms to forge international strategic alliances (ISAs) is unknown. Drawing on organizational ecology and structural inertia theories, this study proposes that the interactions between a firm's structural inertia and environmental hostility are hazardous to firm performance and that ISAs weaken their impacts. Using data from 167 Canadian high-tech firms, this study supports that hypothesis and uncovers important implications for research and practice. Firms' structural inertia makes inconsistency in international product strategies destructive. When structural inertia interacts with the environmental hostility associated with high-tech industries, the impacts can be stronger. High-tech firms resort to ISAs, using their partners to implement different product strategies to avoid adverse outcomes. Thus, ISAs are mechanisms that high-tech firms use to reduce the strategy inconsistencies across countries.